The Influence of Kemak Sanirin Dialect Towards Students’ English Pronunciation - Ati, Martinus Mau; Mujiyanto, Januarius; Suwandi, Suwandi (Universitas Negeri Semarang, 2020)
This qualitative research attempted to review the influence of Kemak Sanirin dialect towards studentsÃ¢â‚¬â„¢ English pronunciation. The objectives of the study were to explain the influence of Kemak Sanirin dialect towards studentsÃ¢â‚¬â„¢ English pronunciation of vowels, consonants, diphthongs, and consonant clusters and to explain the way teachers play their roles to improve studentsÃ¢â‚¬â„¢ pronunciation. This study employed descriptive qualitative method. The subjects of this study were 18 students from eleventh grade students of SMA Negeri 3 Atambua. The data were collected by using questionnaire, studentsÃ¢â‚¬â„¢ recording, observation checklist, and interview. Then, the results of this study show that Kemak Sanirin dialect contributed some positive transfer on vowels (i, Ã‰Âª, u, e, ÃŠÅ , and Ã‰â„¢), insignificant negative transfer on consonants (p, b, k, r, s, g, m, etc.) and siginificant negative transfer on consonant (z), significant positive transfer on diphtongs (eÃ‰Âª, aÃ‰Âª, au) and significant negative transfer on (Ã‰â€Ã‰Âª, Ã‰â€ºÃ‰â„¢, Ã‰â„¢ÃŠÅ , and Ã‰ÂªÃ‰â„¢), significant negative transfer on three consonant clusters, while teacher did play his roles in improving studentsÃ¢â‚¬â„¢ pronunciation.